Cryopreserved platelets in bleeding management in remote hospitals: A clinical feasibility study in Sweden - Wikman, Agneta; Diedrich, Beatrice; Björling, Karl; Forsberg, Per-Olof; Harstad, Anna-Maria; Henningsson, Ragnar; Höglund, Petter; Sköld, Hans; Östman, Lars; Sandgren, Per (Frontiers in Public Health, 2023)
Background Balanced transfusions, including platelets, are critical for bleeding patients to maintain hemostasis. Many rural hospitals have no or limited platelet inventory, with several hours of transport time from larger hospitals. This study aimed to evaluate the feasibility of using cryopreserved platelets that can be stored for years, in remote hospitals with no or limited platelet inventory. Material and methods Three remote hospitals participated in a prospective study including adult bleeding patients where platelet transfusions were indicated. Cryopreserved platelets were prepared in a university hospital, concentrated in 10 ml, transported on dry ice, and stored at −80°C at the receiving hospital. At request, the concentrated platelet units were thawed and diluted in fresh frozen plasma. The indications, blood transfusion needs, and laboratory parameters pre- and post-transfusion, as well as logistics, such as time from request to transfusion and work efforts in preparing cryopreserved platelets, were evaluated. Results Twenty-three bleeding patients were included. Nine patients (39%) were treated for gastrointestinal bleeding, five (22%) for perioperative bleeding, and four (17%) for trauma bleeding. The transfusion needs were 4.9 ± 3.3 red blood cell units, 3.2 ± 2.3 plasma units, and 1.9 ± 2.2 platelet units, whereof cryopreserved were 1.5 ± 1.1 (mean ± SD). One patient had a mild allergic reaction. We could not show the difference in laboratory results between pre- and post-transfusion of the cryopreserved units in the bleeding patients. The mean time from the order of cryopreserved platelets to transfusion was 64 min, with a range from 25 to 180 min. Conclusion Cryopreserved platelets in remote hospitals are logistically feasible in the treatment of bleeding. The ability to have platelets in stock reduces the time to platelet transfusion in bleeding patients where the alternative often is many hours delay. Clinical effectiveness and safety previously shown in other studies are supported in this small feasibility study.